High-Intensity Interval Training Decreases Muscle Sympathetic Nerve Activity in Men With Essential Hypertension and in Normotensive Controls - Ehlers, Thomas Svare; Sverrisdottir, Yrsa; Bangsbo, Jens; Gunnarsson, Thomas Petursson (Frontiers in Neuroscience, 2020)
Exercise training is a cornerstone in reducing blood pressure (BP) and muscle sympathetic nerve activity (MSNA) in individuals with essential hypertension. High-intensity interval training (HIIT) has been shown to be a time efficient alternative to classical continuous training in lowering BP in essential hypertension, but the effect of HIIT on MSNA levels has never been investigated. Leg MSNA responsiveness to six weeks of HIIT was examined in fourteen hypertensive men (HYP; age: 62±7 years, night time BP: 136±12/83±8 mmHg, BMI: 28±3 kg/m2), and ten age-matched normotensive controls (NORM; age: 60±8 years, night time BP: 116±2/68±4 mmHg and BMI: 27±3 kg/m2). Before training, MSNA levels were not different between HYP and NORM (burst frequency (BF): 41.0±10.3 vs. 33.6±10.6 bursts/min and burst incidence (BI): 67.5±19.7 vs. 64.2±17.0 bursts/100 heart beats, respectively). BF decreased (P<0.05) with training by 13 and 5 % in HYP and NORM, respectively, whereas BI decreased by 7% in NORM only, with no difference between groups. Training lowered (P<0.05) night-time mean arterial- and diastolic BP in HYP only (100±8 vs. 97±5, and 82±6 vs. 79±5 mmHg, respectively). The change in HYP was greater (P<0.05) compared to NORM. Training reduced (P<0.05) body mass, visceral fat mass and fat percentage similarly within- and between groups, with no change in fat free mass. Training increased (P<0.05) V̇O2-max in NORM only. Six weeks of HIIT lowered resting MSNA levels in age-matched hyper- and normotensive men, which was paralleled by a significant reduction in BP in the hypertensive men.